Peningkatan Hasil Belajar Matematika Menggunakan Model Project Based Learning (PjBL) di Kelas IV SD - Ardila Oktavia; Nelly Astimar (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2021)
This study aims to describe the application of the Project Based Learning (PjBL) model to improve learning outcomes in the circumference and area of flat shapes in grade 4 Elementary Schools. This type of research is Classroom Action Research (CAR) using qualitative and quantitative approaches. The research subjects were teachers and 32  students in grade 4 of elementary school 16 Padang Besi. The results showed an increase. In the first cycle the observation results of the implementation of learning plans from 82.1% to 92.9% in the second cycle. Implementation on the aspects of teachers and students in the first cycle was 71.9% to 93.8% in the second cycle. The average assessment of student learning outcomes in the first cycle 60.63 to 86.88 in the second cycle.